2015
DOI: 10.1007/s00276-015-1562-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the renal lower pole anatomy and mid-renal-zone classification in successful approach to the calices during flexible ureteroscopy

Abstract: Collecting system with kidney midzone drained by crossed calices presented the lower accessibility rate during FUR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…They experienced relative difficulty in accessing to the calyces of the lower pole in cases with type A2 Sampaio classification when compared to others. [ 18 19 20 ] By announcing a complicated classification system Takazawa et al classified the kidneys based on just CT urography findings in patients under follow-up for hematuria or ureteral tumor. They demonstared only the anatomical data obtained but provided no data regarding the clinical and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They experienced relative difficulty in accessing to the calyces of the lower pole in cases with type A2 Sampaio classification when compared to others. [ 18 19 20 ] By announcing a complicated classification system Takazawa et al classified the kidneys based on just CT urography findings in patients under follow-up for hematuria or ureteral tumor. They demonstared only the anatomical data obtained but provided no data regarding the clinical and surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Atalay et al reported that generating kidney models of PCSs by using 3D printing technology is feasible, and understandings of the disease and the surgical procedure from patients were well appreciated with this novel technology (18). Nevertheless, some other studies showed the importance of the renal anatomy applied to training and execution of the flexible ureteroscopy (19,20). Recently, Marroig et al standardized the building of a three-dimensional silicone mold (cavity) of the collecting system, on the basis of polyester resin endocasts, which can be used in surgical training programs (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of duplicated pelvicalyceal collecting system we analyzed separately the superior and the inferior units. Measurements of width and length of the inferior infundibulum and infundibulum of the minor calyces and the angles were made with the aid of the LibreOffice 6.3 software (15)(16)(17), as shown in Figure -1.…”
Section: Methodsmentioning
confidence: 99%